Ghrelin Augments the Expressions and Secretions of Proinflammatory Adipokines, VEGF120 and MCP‐1, in Differentiated 3T3‐L1 Adipocytes. Issue 1 (January 2015) - Kitahara, Atsuko; Takahashi, Kazuto; Moriya, Rie; Onuma, Hirohisa; Handa, Keiko; Sumitani, Yoshikazu; Tanaka, Toshiaki; Katsuta, Hidenori; Nishida, Susumu; Sakurai, Takuya; Inukai, Kouichi; Ohno, Hideki; et al.
Abstract Ghrelin is a physiological‐active peptide with growth hormone‐releasing activity, orexigenic activity, etc. In addition, the recent study has also suggested that ghrelin possesses the pathophysiological abilities related with type 2 diabetes. However, the ghrelin‐direct‐effects implicated in type 2 diabetes on peripheral tissues have been still unclear, whereas its actions on the central nervous system (CNS) appear to induce the development of diabetes. Thus, to assess its peripheral effects correlated with diabetes, we investigated the regulatory mechanisms about adipokines, which play a central role in inducing peripheral insulin resistance, secreted from mature 3T3‐L1 adipocytes stimulated with ghrelin in vitro . The stimulation with 50 nmol/L ghrelin for 24 h resulted in the significant 1.9‐fold increase on vascular endothelial growth factor‐120 (VEGF120) releases (p < 0.01) and the 1.7‐fold on monocyte chemoattractant protein‐1 (MCP‐1) (p < 0.01) from 3T3‐L1 adipocytes, respectively, while ghrelin failed to enhance tumor necrosis factor‐α (TNF‐α), interleukin‐1β (IL‐1β), IL‐6, IL‐10 and adiponectin secretions. In addition, Akt phosphorylation on Ser473 and c‐Jun NH2‐terminal protein kinase (JNK) phosphorylation on Thr183/Tyr185 were markedly enhanced 1.4‐fold (p < 0.01) and 1.6‐fold (p < 0.01) in the ghrelin‐stimulated adipocytes, respectively. Furthermore, the treatment with LY294002 (50 μmol/L) and Wortmannin (10nmol/L), inhibitors of phosphatidylinositol 3‐kinase (PI3K), significantly decreased the amplified VEGF120 secretion by 29% (p < 0.01) and 28% (p < 0.01) relative to the cells stimulated by ghrelin alone, respectively, whereas these inhibitors had no effects on increased MCP‐1 release. On the other hand, JNK inhibitor SP600125 (10 μmol/L) clearly reduced the increased MCP‐1, but not VEGF120, release by 35% relative to the only ghrelin‐stimulated cells (p < 0.01). In conclusion, ghrelin can enhance the secretions of proinflammatory adipokines, VEGF120 and MCP‐1, but fails to affect IL‐10 and adiponectin which are considered to be anti‐inflammatory adipokines. Moreover, this augmented VEGF120 release is invited through the activation of PI3K pathways and the MCP‐1 is through JNK pathways. Consequently, our results strongly suggest that ghrelin can induce the development of diabetes via its direct‐action in peripheral tissues as well as via in CNS. J. Cell. Physiol. 229: 199–209, 2014. © 2014 Wiley Periodicals, Inc.